Alkylcarbagermatranes Permit an Alkylation-Terminated Catellani Reaction - Jiang, Wei-Tao; Xiao, Bin (Synlett, 2021)
We highlight our recent researches on an alkylation-terminated Catellani reaction using alkylcarbagermatranes. This strategy highlights the unique structure and property of alkylcarbagermatranes and also fills the gap in the Catellani reaction where alkylation termination was missing.
Keywords: organogermanium compounds; carbagermatranes; Catellani reaction; cross-coupling